“The History of the King of Bohemia and His Seven Castles” (1830) by Charles Nodier: When the Language Itself Helps to Translate the Play on Words - Vera A. Milchina (Литературный факт)
At the beginning of 1830, Charles Nodier’s novel, The Story of the King of Bohemia and His Seven Castles, was published in Paris. Even in the 21st century, this novel may seem avant-garde and violates all literary canons and rules. Its narrator appears in three hypostases, which constantly enter into disputes with each other; it mixes a variety of styles and genres; its author accompanies many words with chains of several dozen rhyming synonyms. All this does not make it easier to translate The Story of the King of Bohemia into any language, even a related Romance language, not to mention Russian. Apparently, these features explain the fact that two translations of the novel, into Spanish and English, appeared only in the 21st century, the first in 2016 and the other in 2023, but there is still no translation into Russian. The author of the article is working on a Russian translation of The Story of the King of Bohemia for the “Literary Monuments” series, and the presented note is devoted to one aspect of this work. Oddly enough, it is not about the difficulties of translation (which in this situation would be quite logical) but about its “eases,” that is, about those cases when the Russian language provides the translator with means of word play that are absent in French. For example, neutral “wig heads” (têtes à perruques), which come to life in the novel but behave like stupid idols, when translated into Russian, most naturally become “wig heads” <болваны для париков>, since in Russia in the 18th century this is a hairdressing device was named in this way, but at the same time the word “moron” <болван> had a pejorative meaning: it meant fools (a play on words that is absent not only in French but also in English). The article provides several similar examples, and at the end, it explains why, in the case of Nodier, these examples do not appear to be random luck for the translator, but the implementation of the author’s linguistic utopia.